Study on bolt head corrosion influence on the clamping force loss of high strength bolt. (November 2021) - Li, Ming; Yao, Lingbo; Zhang, Shuoshuo; Wang, Dapeng; He, Zhiqi; Sun, Guohua
Highlights: A stock-removing machine was used to quantitatively simulate the corrosion process. The clamping forces are significantly affected by the bolt head corrosion. The formula for evaluating the clamping force of high strength bolt is proposed. Abstract: High-strength bolts are widely used for connections in steel structures and the load-bearing capacity of such connections is very important for the safety of steel structures. However, numerous traces of corrosion have been observed around high-strength bolt joints of steel structures on site, which can affect the tightening force of these bolts and therefore reduce the bearing capacity of the bolt joints. In this study, the stock-removing machine was used to quantitatively simulate the corrosion of high strength bolt head and the fiber bragg grating sensors were used for obtaining the clamping forces of high strength bolts. Based on the results of numerical simulation and experiments, it is found that fiber bragg grating sensors are reliable and stable for monitoring the clamping forces of high strength bolts while they are installed at the proper location and the clamping forces of high strength bolts are significantly influenced by the bolt head corrosion. The formula for evaluate the clamping force of the high strength bolt with bolt head corrosion is proposed by this study.